A cost-effective smartphone-based device for rapid C-reaction protein (CRP) detection using magnetoelastic immunosensor. Issue 8 (14th March 2023) - Yuan, Zhongyun; Han, Mengshu; Li, Donghao; Hao, Runfang; Guo, Xing; Sang, Shengbo; Zhang, Hongpeng; Ma, Xingyi; Jin, Hu; Xing, Zhijin; Zhao, Chun
Abstract : A smartphone-based C -reaction protein magnetoelastic (CRP-ME) immunosensor was developed. In this study, CRP can be detected with a sensitivity of 12.90 Hz μg −1 mL −1 and detection limit of 2.349 × 10 −4 μg mL −1 . Abstract : C -Reaction protein (CRP) is a marker of nonspecific immunity for vital signs and wound assessment, and it can be used to diagnose infections in clinical medicine. However, measuring CRP level currently requires hospital-based instruments, high-cost reagents, and a complex process, all of which have limited its full capabilities for self-detection, a growing trend in modern medicine. In this study, we developed a novel smartphone-based device using advanced methods of magnetoelastic immunosensing to mitigate these limitations. We combined a system-on-chip (SoC) hardware architecture with smartphone apps to realize the sampling of resonance frequency shift on magnetoelastic chips, which can determine the ultra-sensitivity to mass change caused by the binding of anti-CRP antibody and CRP. Through detecting a multi-group of samples, we found that the resonance frequency shift was linearly proportional to the CRP concentration in the range from 0.1 to 100 μg mL −1, with a sensitivity of 12.90 Hz μg −1 mL −1 and a detection limit of 2.349 × 10 −4 μg mL −1 . Meanwhile, compared with the large-scale instrument used in clinical settings, the performance of our device was stable and significantly more portable, rapid and cost-effective, offering excellent potential for modern home-based diagnosis.